Strategi Distribusi Film Pendek “Anak Lanang” - Firmansyah, Fathoni Fajar; Aulia, Aly; Sudiwijaya, Erwan (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Film is an entertainment medium in the form of audio-visual that can be enjoyed by the audience. In order to be shown, short films must be distributed first. Distribution channels in this digital era, technology has developed a lot, which has resulted in the emergence of various digital-based movie playback platforms, both paid and unpaid, including Iflix, Netflix, Vidio, GoPlay, Genflix, Catchplay, VIU, and Disney+ Hotstar. The purpose of this research is to find out how the distribution strategy of Anak Lanang Film. The research method used in this research is descriptive qualitative research. The theory used is strategy and film distribution. The results of the research obtained are that the Anak Lanang film was originally a final project project which was then directed to the festival and Youtube to be met with the audience. Tito Bagus Ramadhan, the owner of the film project, will pay for the funding from start to finish. The ownership of the Anak Lanang film was handed over to Ravacana Films for distribution. Ravacana Films has never carried out promotions, promotions occurred spontaneously, namely the reaction and attention of the audience when the film Anak Lanang was screened at the festival and also the media that covered the success of the film Anak Lanang at the festivals that were followed. Ravacana Films has never carried out media planning, media relations, media monitoring, and media coverage activities. Festival audiences and Youtube are the target market for the film Anak Lanang. Ravacana has never done cooperation with the film community or individuals in the screening of the Anak Lanang film. The novelty of this research is this research focuses on the distribution strategy used by Film Anak Lanang, including on the Youtube platform. Stating that this thesis is the result of my own work and all I have stated that the sources quoted or referenced are correct.